Comprehensive Expression Profile Analysis of Neutrophil Extracellular Trap-Affected Genes in Gastric Cancer Cells and the Clinical Significance of lncRNA NEAT1-Related Signaling - Li, Changjian; Zou, Xiaoming; Cai, Qingxin; Li, Jiacheng; Yang, Shifeng; Zhang, Ange; Chen, Chongyan; Zhu, Lei (Frontiers in Oncology, 2022)
Background：Gastric cancer (GC) is the fifth largest malignant tumor and the third largest cause of cancer-related death in the world. Neutrophil extracellular traps (NETs) could promote the migration of GC cells and associates with poorer prognosis of patients. However, its mechanisms are incompletely understood. Methods: The content of NETs in peripheral bloods of GC patients was detected by ELISA. GC AGS cells were administered with or without NETs for 24h. High-throughput RNA sequencing were performed to screen differentially expressed long noncoding RNA (lncRNA), microRNA (miRNA) and mRNA. Then real-time PCR experiment were used to verify gene expression. The competing endogenous RNA (ceRNA) regulatory network were constructed. Modules were screened using plug-in MCODE. GO and KEGG enrichment analysis was performed using genes in the network. Then, the role and its clinical significance of lncRNA NEAT1-related signaling pathway was validated. Result: The content of NETs in peripheral bloods of GC patients was significantly higher than that in healthy controls and was also higher in high grade (stage III and IV). NETs promoted the migration of AGS cells. A total of 1340 lncRNA, 315 miRNA and 1083 mRNA were differentially expressed after NETs treatment. The expression of 5 genes were validated using real-time PCR, which is accordance with RNA sequencing results. Then a ceRNA regulatory network was constructed with 1239 lncRNA, 310 miRNA and 1009 mRNA. Four genes (RAB3B, EPB41L4B, ABCB11 and CCDC88A) in the ceRNA network were associated with prognosis of patients and RAB3B was the most prominent one. LncRNA NEAT1/ miR-3158-5p/ RAB3B signaling was exist in the ceRNA network. LncRNA NEAT1 was upregulated in AGS cells after NETs treatment. The interference of lncRNA NEAT1 inhibited the migration of AGS cells-induced by NETs, also inhibited miR-3158-5p expression and promoted RAB3B expression. The expression of lncRNA NEAT1 and RAB3B was positively correlated in GC patients. Furthermore, RAB3B was upregulated and miR-3158-5p was down regulated in GC tissues compared with adjacent normal tissues, which was also associated with cancer stage. Conclusion: This study provides a comprehensive analysis of differentially expressed genes in NETs-treated GC cells, and validated the clinical significance of lncRNA NEAT1-related signaling.